(untitled) (Asian Journal of Medical and Biological Research, 2024)
The process of fish drying in Char Patharghata, Chattagram district, and its distribution channels serve as vital components of the local economy. This study aims to delve into the intricacies of this process, analyzing the activities of each value chain actor from raw fish supplier to dry fish consumer. Through the analysis of various value chain actors, from fishermen to consumers, the study seeks to uncover insights into the dynamics of this industry. From January 2022 to August 2022, semi-structured questionnaires were employed to gather data for this study. Seven main value chain actors were identified, including fishermen, processing center owners, processors, Aratdars, wholesalers, retailers, and consumers. Interviews were conducted with 19 fishermen, 5 owners of dry fish processing industries, 48 processors, 25 Aratdars, 15 wholesalers, 18 retailers, and 22 consumers, selected randomly. The study revealed that a significant proportion of fishermen were illiterate and employed on a contractual basis by fishing vessel owners. Additionally, a substantial majority of dried fish processors were female, with disparities observed in wages between male and female workers. During the observed timeframe, a total of 19 species spanning 14 families were noted to be utilized for drying. Notably, Churi (Lepturacanthus savala), Phaisa (Setipinna phasa), and Hangor (Scoliodon sorrakowah) emerged as the predominant species in this process, with concerns raised regarding the maintenance of dried fish quality. The dried fish industry holds considerable economic importance in the local community, with high consumption rates among residents. However, challenges exist in maintaining the quality of dried fish products. Recommendations are proposed to improve the quality of dry fish and enhance the livelihood standards of fishers, processors, and other stakeholders involved in the processing and distribution of dried fish. These measures aim to foster sustainable growth and development within the industry, benefiting both producers and consumers. Asian J. Med. Biol. Res. 2024, 10(1), 42-57